PENGARUH EFISIENSI, KEMUDAHAN, DAN KEAMANAN INFORMASI TERHADAP MINAT MENGGUNAKAN APLIKASI FINTECH - Fikri Akbar; Sakum; Solikhul Hidayat (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
This study aims to determine how the effect of efficiency, convenience, and information security on interest in using fintech applications. The population of this study were students of the Faculty of Islamic Religion, Pelita Bangsa University with a sample of 130 people. Primary data obtained from respondents via Google Docs. The sampling technique used was purposive sampling method and the analytical technique used was multiple linear regression test. The results showed that the efficiency variable had a positive and significant effect on interest in using fintech applications. The convenience variable has a positive and significant effect on interest in using fintech applications. And the information security variable has a positive and significant effect on interest in using fintech applications. And from the results of the determination test, it can be stated that efficiency, convenience, and information security have a simultaneous effect on interest in using fintech applications.